Exploring Self-Care and Preferred Supports for Adult Parents in Recovery from Substance Use Disorders: Qualitative Findings from a Feasibility Study. (2nd November 2017) - Raynor, Phyllis A.; Pope, Charlene; York, Janet; Smith, Gigi; Mueller, Martina
ABSTRACT: Very little is known about the self-care behaviors (SCB) that adult parents employ and the preferred supports they utilize to maintain their recovery from substance use disorders (SUD) while also parenting their children. This study used a qualitative descriptive approach to explore perceptions of self-care and parenting to inform future self-care interventions for parents in early recovery. Nineteen mothers and fathers of at least one child between the ages of 6–18 were interviewed by telephone about parental self-care practices while in recovery from SUD, recovery management, and preferred supports in the community. Participants described the experience of parenting as challenging, with variations in the level of support and resources. Self-care included meaningful connection with recovery support and children, taking care of physical health, maintaining spirituality, healthy eating, exercise, journaling, continuing education, staying busy, sponsorship, establishing boundaries, self-monitoring, abstinence, and dealing with destructive emotions. Participants reported SCB as being a critical component of their ongoing recovery and their parenting practices, though differences in SCB by gender and for minorities require further exploration. Parental gains were perceived as benefits of SCB that minimized the negative impact of prior parental drug use on their children.